Can the Indicative Price System Mitigate Expiration‐Day Effects?. Issue 10 (13th July 2012) - Chay, J.B.; Kim, Sol; Ryu, Hyeuk‐Sun
<x xml:space="preserve">Abstract</x> We investigate whether the indicative price system, introduced in the Korean derivatives market on July 1, 2003, has helped mitigate the options and futures expiration‐day effects. Prior to introduction of this system, we find evidence of high trading volume and significant price reversals during the first half hour of trading for the day immediately following the expiration day. These effects decline significantly after July 1, 2003. Our evidence suggests that the indicative price system can mitigate the expiration‐day effects.